Behavior of anastomozed vessels and transferred flaps after anastomosed site infection in head and neck microsurgical reconstruction. Issue 8 (21st January 2016) - Kubo, Tateki; Matsuda, Ken; Kiya, Koichiro; Hosokawa, Ko
Abstract : Objective: This report evaluates the behavior of anastomosed vessels and transferred flaps after anastomosed site infection in head and neck reconstruction. Patients and methods: Eleven free‐flap cases after infection at the vascular pedicle site were included, the patency of which was observed macroscopically after re‐exploration and pus drainage. Location was in the tongue (5 cases), oropharynx (3 cases), mouth floor (1 case), mandible (1 case), and hypopharynx (1 case). Transferred flaps originated from rectus abdominis (3 cases), anterolateral thigh (3 cases), radial forearm (3 cases), jejunum (1 case), and latissimus dorsi (1 case). Days for infection found were ranged 3–14 days postoperatively. Causes of infection were the salivary fistula formation in 5 cases, and precise etiology was not defined in the other 6 cases. Results: Disruption of the vascular pedicles occurred with high frequency after infection. Disruption of vein occurred most frequently (5 cases), followed by both artery and vein (2 cases) and artery only (1 case). Of the eight flaps, two flaps failed, but the other six flaps survived despite pedicle disruption, indicating overall survival of nine flaps after pedicle site infection. Five of the nine survived cases were healed with simple washing and ointment application. However, the other four patients, whose cause of infection was a salivary fistula, needed second flap transfer to treat those fistulas. Conclusion: Disruption of anastomosed vessels can occur with high frequency after infection, causing subsequent flap loss. Therefore, surgeons need to deal with pedicle site infection to save the flap. © 2015 Wiley Periodicals, Inc. Microsurgery 36:658–663, 2016.